2016
DOI: 10.1007/s00417-016-3353-7
|View full text |Cite
|
Sign up to set email alerts
|

Twelve-month outcomes of treatment using ranibizumab or aflibercept for neovascular age-related macular degeneration: a comparative study

Abstract: The 12-month treatment outcome of intravitreal ranibizumab was similar to that of intravitreal aflibercept, with a comparable injection frequency. Further prospective studies with a more controlled design are needed to confirm our findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
21
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 28 publications
4
21
1
1
Order By: Relevance
“…Sixty‐three studies were summarized in the data collection sheet after 31 studies were excluded based on exclusion criteria. Prior to the meta‐analysis, 21 studies were excluded due to missing statistical parameters, resulting in 42 studies; 11 RCTs and 31 observational studies (Figure , Table ) were included in statistical analyses.…”
Section: Resultsmentioning
confidence: 99%
“…Sixty‐three studies were summarized in the data collection sheet after 31 studies were excluded based on exclusion criteria. Prior to the meta‐analysis, 21 studies were excluded due to missing statistical parameters, resulting in 42 studies; 11 RCTs and 31 observational studies (Figure , Table ) were included in statistical analyses.…”
Section: Resultsmentioning
confidence: 99%
“…29 Because the National Health Insurance system of South Korea covers a limited number of ranibizumab injections, the number of injections in our study might have been lower than that in other countries as shown in another study in South Korea. 30 In addition, the exclusion of PCV might have reduced the number of injections because there are cases that require frequent injections. 31 In addition, there were still 28 eyes (43.1%) with SHRM at month 12, and half of them had increased SHRM volumes with significantly lower increases of BCVA.…”
Section: Discussionmentioning
confidence: 99%
“…Ranibizumab was approved in Korea by the Ministry of Food and Drug Safety on 27 July 2007 for the treatment of nAMD. Although several small studies have investigated the efficacy and safety of ranibizumab in Korean patients with nAMD since its approval [678], no large-scale data are available. This regulatory post-marketing surveillance (PMS) study was therefore conducted to evaluate the safety and efficacy of ranibizumab in Korean patients.…”
mentioning
confidence: 99%
“…This regulatory post-marketing surveillance (PMS) study was therefore conducted to evaluate the safety and efficacy of ranibizumab in Korean patients. Whereas most of the studies on Asian nAMD patients have taken place either in an RCT setting or retrospectively and have been limited by the small number of patients [678910], the strength of this PMS study lies in the enrollment of a large number of Korean patients from nearly all the centers specialized for retina care in South Korea. Furthermore, by enrolling patients who would not have met the strict inclusion criteria of an RCT, the PMS study ref lects the real-world efficacy and safety of ranibizumab for nAMD in South Korea.…”
mentioning
confidence: 99%